Defining psychosocial strength and conditioning coaching competencies: A participatory action research approach. Issue 2 (April 2023) - Callary, Bettina; Gearity, Brian T; Eagles, Kimberley; Szedlak, Christoph
Strength and conditioning (S&C) practitioners need to know and apply varying and diverse psychosocial competencies in their practice. The definitions of psychosocial coaching competencies are poorly understood and multiple interpretations exist. The purpose of this study was to define psychosocial S&C practice terms (i.e. pedagogical, philosophical, psychological, sociocultural) from the perspectives of S&C researchers and practitioners. Using a participatory action research approach, qualitative data were collected from 13 researchers and 30 stakeholders with the United Kingdom Strength and Conditioning Association (UKSCA). A qualitative summative content analysis was used to analyze the researchers' and UKSCA stakeholders' definitions of psychosocial competencies. Pedagogical competencies were defined related to the themes of instruction, learning, skill acquisition, feedback, and design structure. Philosophical competencies were defined related to themes of beliefs, values, and style. Psychological competencies were defined related to communication, mindset, relationships, motivation, emotions, learning, and behavior. Sociocultural competencies were defined related to sport norms, understanding differences and different backgrounds, adapting to culture, and coaching behavior and biases. Significant differences existed between researchers' and practitioners' definitions of these terms, particularly with pedagogical, philosophical, and sociocultural competencies. Practitioners often associated psychological coaching competencies with subject matter outside of biophysical knowledge or many aspects spanning diverse social and behavioral sciences.